Post-harvest factors involved in the development of woolliness in nectarines (Prunus persica) - Von Mollendorff, Leon Johann (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D. Agric.) -- University of Stellenbosch, 1991.